Depletion of ozone and reservoir species of chlorine and nitrogen oxide in the lower Antarctic polar vortex measured from aircraft - Jurkat, Tina; Voigt, Christiane; Hüneke, Tilman; Pfeilsticker, Klaus (Geophysical research letters, 2017)
Novel airborne in situ measurements of inorganic chlorine, nitrogen oxide species, and ozone were performed inside the lower Antarctic polar vortex and at its edge in September 2012. We focus on one flight during the Transport and Composition of the LMS/Earth System Model Validation (TACTS/ESMVal) campaign with the German research aircraft HALO (High-Altitude LOng range research aircraft), reaching latitudes of 65°S and potential temperatures up to 405 K. Using the early winter correlations of reactive trace gases with N2O from the Atmospheric Chemistry Experiment-Fourier Transform Spectrometer (ACE-FTS), we find high depletion of chlorine reservoir gases up to ∼40% (0.8 ppbv) at 12 km to 14 km altitude in the vortex and 0.4 ppbv at the edge in subsided stratospheric air with mean ages up to 4.5 years. We observe denitrification of up to 4 ppbv, while ozone was depleted by 1.2 ppmv at potential temperatures as low as 380 K. The advanced instrumentation aboard HALO enables high-resolution measurements with implications for the oxidation capacity of the lowermost stratosphere.